Uprzemysłowienie województwa białostockiego w planie sześcioletnim. Zamierzenia i efekty - Zawistowski, Andrzej (Pamięć i Sprawiedliwość, 2008)
In the 1950s, the Polish communist authorities leading the country’s industrialization, declaimed the principals of evenly distributed industry with the aim of activating poorly industrialized territories. Such principles were particularly attractive to the Białystok Voivodship. The six-year plan foresaw that over 80 large enterprises would arise in the Białystok Voivodship. Industrial development was to be concentrated in the so-called ‘industrial triangle’, demarked by Białystok, Ełk and Łomża. These towns were to become, according to the six-year plan, the main industrial centers of the Voivodship, infl uencing smaller towns linkedto them through communication and industry. Corrections to the six-year plan, introduced by the government in 1951 and 1952, caused many investments to be abandoned. The Voivodship that lost the most investments was Białystok (as many as 67 investments were abandoned, in Lublin and Kraków Voivodship only 21 each). Despite limiting investments, during the six-year plan in Białystok the followingimportant key industrial enterprises were built, or partially built: ZakładyPrzemysłu Bawełnianego „Fasty” in Białystok, Zambrowskie Zakłady Przemysłu Bawełnianego, Ełckie Zakłady Roszarnicze, Fabryka Przyrządów i Uchwytów in Białystok, Białostockie Zakłady Piwowarsko-Słodownicze, Zakłady Piwowarsko-Słodownicze in Suwałki, Mazurska Wytwórnia Tytoniu Przemysłowego in Augustów, Mielnickie Terenowe Zakłady Kredowe in Mielnik, and the lumber mill in Czarna Białostocka.On the example of the Białystok Voivodship it is clear that the officiallydeclaimed and widely publicized through propaganda goal of the six-year plan (to even out the country’s internal economic disproportions) were not achieved. Investment outlay in an economy socialized at the moment of the six-year plan’s start in the Białystok Voivodship were the lowest of all voivodships. An atmosphere more favorable to production industry geared toward consumer goods allowed the Voivodship to benefi t from the six-year plan. Independent from political, economic and social opinions, the six-year plan should be recognized that it became a breakthrough moment for the Białystok Voivodship (region).